Malfunction of Vascular Control in Lifestyle-Related Diseases: Endothelial Nitric Oxide (NO) Synthase/NO System in Atherosclerosis - Seinosuke Kawashima (Elsevier, 2004)
Nitric oxide (NO) from the endothelial NO synthase (eNOS) is believed to be implicated in the development and progression of atherosclerosis. The impaired endothelium-dependent vasodilatory response (EDR) has been demonstrated in vessels exposed to hypercholesterolemia and atherosclerosis. The extent of impairment serves as a predictor of future progression of atherosclerosis. As to the mechanisms of impaired EDR, increased production of superoxide is important. Recently it was revealed that eNOS becomes dysfunctional and produces superoxide rather than NO under conditions in which vascular tissue levels of tetrahydrobiopterin (BH4), a co-factor for eNOS, are deficient or lacking. Dysfunctional eNOS is closely implicated in the endothelial dysfunction represented by impaired EDR in various vascular disorders including atherosclerosis. Regarding the role of eNOS in atherogenesis, experimental studies in vitro have revealed that NO from eNOS constitutes as an anti-atherogenic molecule. In eNOS-knockout mice, eNOS deficiency augments atherosclerotic lesion formation, although the effects may be partly due to the associated hypertension. However, in eNOS-transgenic mice (eNOS-Tg) crossbred with apolipoprotein E-deficient mice (apoE-KO/eNOS-Tg), we found the accelerated lesion formation in association with increased superoxide production from vessels compared with apoE-KO mice. The vascular tissue levels of BH4 were reduced and BH2, an oxidized form, levels were increased. Chronic administration of exogenous BH4 or overexpression of GTPCH-1, a rate limiting enzyme for BH4 synthesis, restored the lesion to the levels comparable to apoE-KO mice. Therefore, eNOS may have two faces in the pathophysiology of atherosclerosis depending on tissue BH4 levels. Keywords:: nitric oxide (NO), superoxide, endothelial NO synthase, atherosclerosis, tetrahydrobiopterin